PENGETAHUAN IBU TENTANG STUNTING PADA BALITA DI DESA LUBUK BILANG KECAMATAN RAMBAH SAMO KABUPATEN ROKAN HULU - Herawati, Rika; lia fitri, yusma; Andria, Andria (Maternity and Neonatal : Jurnal Kebidanan, 2022)
Stunting can be defined as a condition where a person's height does not match the age that has beendetermined by calculating the Z-Index score for Height by Age (TB/U). A person is said to be stunted ifthe Z-index TB/U score is below -2 SD (standard deviation) (Sutarto, Mayasari, & Indriyani, 2018). Thepurpose of this study was to determine the description of maternal knowledge about stunting in toddlersin Lubuk Bilang village. Rambah Samo sub-district, Rokan Hulu district. This research method usesdescriptive with cross sectional design. The sampling technique was carried out using total sampling,that is, all the population was sampled. In this study, the number of samples was 35 mothers who hadstunting toddlers. The analysis of this study used Univariate analysis. The results of this study showedthat the respondent's knowledge about stunting was categorized as less, the age with less knowledge,namely the age of 20-35 years, amounted to 27 people (77%), those with less knowledge based on theireducation were 14 elementary school students (40%), and the knowledgeable less based on occupationare housewives (IRT) totaling 20 people (57%). The conclusion of this study was that the mother'sknowledge about stunting in children under five in Lubuk Bilang village was said to be lacking, based onage, education and occupation.Keywords: Knowledge, Stunting, Lubuk Bilang Village